EFEKTIFITAS EDUKASI KESEHATAN TERINTEGRASI PADA PASIEN PRE DAN POST OPERASI PANGGUL : LITERATURE REVIEW: The Effectiveness of Integrated Health Education Among Patient Undergo Pre and Post Hip Surgery: A Literature Review - Anas Khafid; Riri Maria (Jurnal Ilmiah Keperawatan (Scientific Journal of Nursing), 2020)
Introduction: Hip fracture is a major problem in the elderly throughout the world. Hip arthroplasty is a procedure when treatment and physical therapy are no longer effective. Health education delivers by health care professionals who less will have an impact on the short and long term both physically and mentally. The purpose of this literature review is to explore the effectiveness of health education among patients who undergo pre and post hip surgery. Method: Literature research conducted on the five largest databases consist of Pubmed, Google Scholar, CINAHL, Medline and PsycINFO using medical subject headings "Health Education", "Patient Education", "Educational", "Hip Surgery", "Hip Arthroplasty" and "Health Education and Hip Arthroplasty ". The combination of keywords searches to find more specific literature. Results: We found 20 articles and five articles are analyzed further. Seven effects of health education impacted knowledge and behavior, pain, Activity Daily Living (ADL), quality of life, function, hip healing and length of stay, self-efficacy and depression. Discussion: Health education requires the appropriate media, duration and integrated methods; therefore, it will increase the recovery and rehabilitation process. Five studies showed the effectiveness of education in patients with hip surgery and the result of each study reinforcing each other.